PENDAMPINGAN SERTIFIKASI HALAL MELALUI SKEMA SELF DECLARE PADA PRODUK UMKM - Isnaini Julianti; Selly Marcella; Annisa Humaira; Dony Burhan Noor Hasan (Universitas Al-Amien Prenduan, 2023)
The main activity in this community service is assistance to prepare UMK to obtain halal certification from LPPOM MUI. The government through the Ministry of Religion and BPJPH (Halal Product Guarantee Management Agency) launched the Free Halal Certification (Sehati) program for UMK to make it easier for UMK to obtain halal certification. The approach used in this service is descriptive qualitative research using field research. The method used in this service includes providing direct information regarding the urgency of informal halal certification for a product as well as direct assistance to UMK in the process of completing halal certification. The mentoring process went quite smoothly because UMK were very cooperative. The business actors involved were enthusiastic about the assistance and knowledge about halal product processes during the activity.Â Â